Detection of Groundnut ringspot virus carried by Frankliniella sp. on watermelon fields in Brazilian Cerrado - Queiroz, Ananias; Romero, Melissa Alexandra; Santos, Gil; Aguiar, Raimundo Wagner (Revista de Ciencias Agrícolas, 2023)
Citrullus lanatus (Thunb.) is an important crop in Brazil and affected by relevant insect vectors, including thrips (Thysanoptera: Thripidae). The present work was focused on evaluating the presence of Groundnut ringspot virus (GRSV) associated with Frankliniella sp. (Thysanoptera: Thripidae) in watermelon, C. lanatus, cultivated in the Brazilian Cerrado biome. Several species of thrips were collected from four commercial crops located in Gurupi, Lagoa da Confusão, Formoso do Araguaia and Porto Nacional counties, all of them belonging to the Brazilian state of Tocantins). The total viral RNA obtained from the thrips was enriched and used to perform ugh RT-PCR. Using specific primers, a 644 bp fragment of the GRSV nucleocapsid was identified in all insect samples, which allowed us to perform a phylogenetic analysis with GRSV sequences described for other geographical regions. The findings demonstrate the wide distribution of the GRSV virus in commercial watermelon crops in the Brazilian Cerrado Biome. The association with Frankliniella sp. is highlighted as one of the most relevant vector pathways in this region of high intensity and advanced agriculture. In addition, phylogenetic analysis demonstrated a close relationship between GRSV sequences from South Africa and Brazil. These findings may contribute to the understanding of GRSV distribution in watermelon crops in different localities of Brazilian Cerrado Biome.